Analisis Kebijakan Kurikulum Pendidikan Islam di Lembaga Pendidikan Islam - Khoiruddin, Moh. (JOIES (Journal of Islamic Education Studies), 2016)
Curriculum of Islamic education in Indonesia, especially in an environment absolutely unique educational institution that is popular with characteristic of traditionality.Predicate Islam, automatically and logically consequence, that the educational curriculum as intended must have characteristics that set it apart than other types or categories. Islamic education curriculum must be in harmony with the basic principles of Islamic education and the basic principles of Islam. The diversity of Islamic education institutions, led to divergent curricula in Islamic educational institutions, such as schools, madrassas, Islamic schools, and universities tingggi Islam. The diversity of the curriculum of Islamic education institutions, which is caused differences in educational objectives, principles of curriculum development and curriculum and selection. Islamic education curriculum in terms of Islamic education policy analysis, can be seen from the three models, the model of a prospective, retrospective and model of integrative models. Curriculum pesantren and madrasah curriculum should at least use the integrative models where the model is able to combine the two previous models, so that education Islamic schools remain a role model for public education by promoting Islamic education.